Emergência, distribuição espacial e manejo de buva resistente ao herbicida glifosato - Machado, Rodrigo Tascheto (2014)
The knowledge of spatial distribution in weed populations allows site specific management that can entail economic benefits of materials, and preservation of the environment. The objective of this study is to evaluate the emergence flow, spatial distribution with utilization of maps, and chemical and mechanical management on horseweed (Conyza bonariensis and Conyza Canadensis) resistant to herbicide glyphosate. The first analysis has samples from previously harvested soybean sites in the municipality of Cruz Alta and São Gabriel, Rio Grande do Sul, Brazil; with an area of 9.47 and of 4.98 ha, respectively. The samples were taken from each sample point of 0.50 x 0.50m by counting the number of horseweed presented. The analysis of the spatial distribution was done with semivariograms in different emergence flows of horseweed with a map generated by the software program ArcGis 9.3, and spatial dependence was estimated by classification of Cambardella et al. (1994). The second analysis consisted of six treatments: two mechanical managements (plowing followed by harrowing and harrowing one-way); three chemical managements (glyphosate + 2,4-D®, glyphosate + saflufenacil, and glyphosate alone), and a control without management. The weeds Conyza bonariensis and Conyza canadensis presented in the experimental area were in the reproductive phase with an average height of 75cm and 80% soil coverage. The evaluation of the experiment was performed in 7, 14 and 28 days after application of treatment (DAT). The treatment of glyphosate alone was unsuccessful, thus confirming that the weeds have developed a resistance to the chemical. The combinations between the herbicides of 2,4-D® and saflufenacil with glyphosate propitiated significant increases in the control of horseweed. The mechanical management (plowing followed by harrowing) obtained total control of horseweed. The chemical treatments, with exception to glyphosate, can be recommended for the management of horseweed in pre-sowed soybeans.